Petri Net Reduction Using Association Rules Technique (Al-Mansour Journal, 2022)
There are several techniques to reduce Petri nets which play important roles in wide application areas. This paper presents a new approach to reduce the Petri nets. The suggested approach depends on converting the Petri nets to logic programs, then process the production rules of logic programs using association rules technique with Apriori algorithm to extract the logical relations of these production rules which allows to reduce the logic program. At last, the Petri nets are reconstruct from reduced logic programs to produce reduced Petri nets. The experimental results show that the suggested approach is a good, efficient and logical technique to reduce the Petri nets.